Nutrition Education on Sedentary Activity for Adolescent - Insani, Hurry Mega; Kustiyah, Lilik; Dwiriani, Cesilia Meti; Sentanu, Mutiara Ayu (Universitas Pendidikan Indonesia, 2021)
Adolescents are prone to nutrition problem, such as the lack of nutrition, overweight, and obesity caused by sedentary behaviours. Adolescents’ activities are influenced by their surrounding environment, such as family, friends, and duration of gadget use. Nutrition Education is a method to help increasing the adolescent’s knowledge about the importance of increasing physical activity and the consequence of sedentary behaviours for adolescents. Knowing the most effective method was the purpose of the study. This study used a quasi-experimental method with control group pre-test post-test design. The study was carried on three groups of adolescents, namely the lecture group, website group, and control group, for two months on school days. The instrument used was ASAQ (Adolescents Sedentary Activity Questionnaire) analysed by one-way ANOVA. The subjects of this study were adolescents aged 15-16 years old. This study used purposive sampling to select the subjects. The results showed that Nutrition Education using the interpersonal lecture method could increase 23.7 points of adolescent knowledge compared to Nutrition Education using the website method (6.2 points). Nutrition Education could increase the adolescent’s knowledge but it did not have a significant effect on adolescent’s physical activity on school days. Some activities of the adolescents were quite high, especially the learning activities of the lecture group (471.7 ± 53.5) and the website group (471.7 ± 53.5). The sleep activity also increased significantly in the lecture group (p = 0.040), website group (p = 0.003), and control group (p = 0.015). Meanwhile, the screen time activity decreased significantly (p = 0.011) in the lecture group due to various factors. Further research related to the factors affecting the duration of adolescent’s screen time on school days needs to be conducted.